Making OTC Derivatives Safe-A Fresh Look - Singh, Manmohan (IMF Working Papers; Working Paper, 2011)
Recent regulatory efforts, especially in the U.S. and Europe, are aimed at reducing moral hazard so that the next financial crisis is not bailed out by tax payers. This paper looks at the possibility that central counterparties (CCPs) may be too-big-to-fail entities in the making. The present regulatory and reform efforts may not remove the systemic risk from OTC derivatives but rather shift them from banks to CCPs. Under the present regulatory overhaul, the OTC derivative market could become more fragmented. Furthermore, another taxpayer bailout cannot be ruled out. A reexamination of the two key issues of (i) the interoperability of CCPs, and (ii) the cost of moving to CCPs with access to central bank funding, indicates that the proposed changes may not provide the best solution. The paper suggests that a tax on derivative liabilities could make the OTC derivatives market safer, particularly in the transition to a stable clearing infrastructure. It also suggests reconsideration of a "public utility" model for the OTC market infrastructure.